Posterior Extra-articular Ischiofemoral Impingement Can Be Caused by the Lesser and Greater Trochanter in Patients With Increased Femoral Version: Dynamic 3D CT–Based Hip Impingement Simulation of a Modified FABER Test - Lerch, Till D. (Orthop J Sports Med, 2021)
BACKGROUND: Posterior extra-articular hip impingement has been described for valgus hips with increased femoral version (FV). These patients can present clinically with lack of external rotation (ER) and extension and with a positive posterior impingement test. But we do not know the effect of the combination of deformities, and the impingement location in early flexion is unknown. PURPOSE: To evaluate patient-specific 3-dimensional computed tomography (3D CT) scans of hips with increased FV and control hips for differences in range of motion, location and prevalence of osseous posterior intra- and extra-articular hip impingement. STUDY DESIGN: Case series; Level of evidence, 4. METHODS: Osseous 3D models based on segmentation of 3D CT scans were analyzed for 52 hips (38 symptomatic patients) with positive posterior impingement test and increased FV (>35°). There were 26 hips with an increased McKibbin instability index >70 (unstable hips). Patients were mainly female (96%), with an age range of 18 to 45 years. Of them, 21 hips had isolated increased FV (>35°); 22 hips had increased FV and increased acetabular version (AV; >25°); and 9 valgus hips (caput-collum-diaphyseal angle >139°) had increased FV and increased AV. The control group consisted of 20 hips with normal FV, normal AV, and no valgus (caput-collum-diaphyseal angle <139°). Validated 3D CT–based collision detection software for impingement simulation was used to calculate impingement-free range of motion and location of hip impingement. Surgical treatment was performed after the 3D CT–based impingement simulation in 27 hips (52%). RESULTS: Hips with increased FV had significantly (P < .001) decreased extension and ER at 90° of flexion as compared with the control group. Posterior impingement was extra-articular (92%) in hips with increased FV. Valgus hips with increased FV and AV had combined intra- and extra-articular impingement. Posterior hip impingement occurred between the ischium and the lesser trochanter at 20° of extension and 20° of ER. Impingement was located between the ischium and the greater trochanter or intertrochanteric area at 20° of flexion and 40° of ER, with a modification of the flexion-abduction-ER (FABER) test. CONCLUSION: Posterior extra-articular ischiofemoral hip impingement can be caused by the lesser and greater trochanter or the intertrochanteric region. We recommend performing the modified FABER test during clinical examination in addition to the posterior impingement test for female patients with high FV. In addition, 3D CT can help for surgical planning, such as femoral derotation osteotomy and/or hip arthroscopy or resection of the lesser trochanter.